Формирование эффективной групповой (парной) работы через критериальное оценивание - Жакупова, Б.К. (My University, 2016)
Teachers of Zatobol school 1 made a big research in form Lesson Study. Four groups were finding optimal ways of group (partner) works according criteria evaluation. The results of this research were approbate by certificates’ teachers of school. Materials were find in almanac of opened lessons, and booklet of rubricates and methodological recommendations.
Keywords: lesson; research; collective; criteria’s; evaluation; group